Nanotextured Morphology of Poly(methyl methacrylate) and Ultraviolet Curable Poly(urethane acrylate) Blends via Phase Separation. (18th October 2015) - Kim, Ju-Hyung; Kim, Joon H.; Seo, Soonmin
Abstract : Domain structures of spin-coated immiscible poly(methyl methacrylate) (PMMA) and ultraviolet (UV) curable poly(urethane acrylate) (PUA) blends were studied using atomic force microscopy (AFM). Spin casting the PMMA/PUA blends in propylene glycol monomethyl ether acetate (PGMEA) was accompanied with phase separation, and PUA was subsequently cross-linked under UV radiation. Selective dissolution of PMMA in the phase-separated films was feasible using tetrahydrofuran (THF) solvent after the UV curing process, because the cured PUA material is highly stable against THF. Morphology of phase-separated structure, including domain size and height, could be controlled by varying total concentration of the blended solution, and various nanoscale features such as island-like and hole-like structures were achieved by changing weight ratio of the two immiscible polymers.